Modeling of Consciences Image "Government / Elite" by Tatars and Russians (Evidence from of the Republic of Tatarstan) - Stankevich, Ekaterina A.; Khanova, Aigul F.; Gallyamov, Filus G. (Journal of History Culture and Art Research, 2017)
In this article inter-ethnic tension in government sphere is detected. Consideration of the concept of inter-ethnic tension from the position of psycholinguistics provides additional material for a comprehensive study of this issue, an attempt is made to diagnose inter-ethnic tensions in a particular region - the Republic of Tatarstan. As stimulus - word was taken the following group: Ethno-social representations associated with public notions: pravitel'stvo/hökümät-government/elite. Psycholinguistics (ethno-psycholinguistics), which deals with the problem of representation of the systemic nature of the linguistic consciousness of native speakers of different cultures, puts forward the associative experiment as the main method. The material of the study is an array of associates, which we obtained as a result of a free associative experiment in Russian and Tatar languages. We placed our research on the Internet site http://virtualexs.ru. The experiment was conducted in 2015 and 2016. Analyzing the data obtained during the free associative experiment, we come to the conclusion that the situation between the title and non-title ethnic group is not ethnically tense. We can predict: if the effectiveness of the state national policy remains at the same low level, inter-ethnic tension in society will grow, and the geography of conflicts will expand.